Evaluation of Depression and Anxiety in patients with tinnitus - S.A.A. Hosseininasab, M.D; F. Sheykhmounesi, M.D; R. Pourmousa, M.D; S. H. Hosseini, M.D (Journal of Mazandaran University of Medical Sciences, 2008)
AbstractBackground and Purpose: Tinnitus is a troublesome disease that may cause several problems, including the following: insomnia decreased concentration and diminished quality of life. This study was designed in order to evaluate depression and anxiety in patients with tinnitus.Materials and Methods: This study was an experimental survey and carried out with case – control method. There were 50 persons in case and control groups, case group included patients with non-organic tinnitus. The patients in case and control group completed Beck and Spiel Berger questionnaire, in order to evaluate their level of depression and anxiety.Results: Age, sex, marital status and smoking of case and control groups were similar. Case groups included 50 patients in which 20 of those were smokers and their level of depression and anxiety were higher than non smokers and this difference was significant (P=0.03). Level of depression in patients with tinnitus was higher than control group (p=0.03), patients with tinnitus experienced more anxiety than control group.Conclusion: The patients with tinnitus suffered more depression and anxiety in comparison to patients without tinnitus.